Characterization and evaluation of heat treated wheat flours - Khamis, Moses (Kansas State University, 2014)
The concept of thermal processing of foodstuffs has been used extensively since 1920 when the first scientific basis for calculating the minimum safe sterilization process was developed. There are several methods used in thermal processing of dry foods including infrared, microwave, hydrothermal treatments such as annealing and heat-moisture treatment, thermomechanical treatments (extrusion), and indirect (hot air) and indirect (steam) heating. Thermal processing has been the most widely used method for preserving and extending the shelf-life (via microbial reduction and enzyme inactivation, and for improving quality and functionality. In 2009 the Centers for Disease Control and Prevention released a report of an Escherichia coli outbreak resulting from consumers eating raw refrigerated cookie dough which brought attention to heat treatment of flours and powders. Chlorination of wheat flour in the European Union countries has been replaced in recent years by heat-treated flour which is used to produce high ratio cakes. By applying heat treatment, it is possible to modify the physical and rheological properties. The primary effect of heat treatment is denaturation of the proteins, partial reduction or inactivation of alpha-amylase, and partial gelatinization of the starch. Understanding of relationship between heat transfer, thermal properties of food, heating medium, thermodynamics and the functionality of the resulting heat-treated flour is of critical importance. Research reported in this dissertation has five chapters. Chapter 1 provides a general overview on the state-of-knowledge in the area. Chapter 2 focuses on developing a thermomechanical treatment (extrusion) for improving the functionality of low quality (ash > 1.3%) wheat flour. Chapter 3 deals with developing a direct, rapid and continuous thermal processing technique for treating whole wheat flour and whole wheat grain, and investigates physicochemical changes of heat-treated samples at various moisture-time-temperature combinations. Chapter 4 explores the mixing and development of composite flours in the presence of gluten fractions of at varying proportions, mixing speed and temperatures. Chapter 5 highlights general conclusions and identifies areas for future research.
Keywords: Heat treatment whole grain flour; Food Science (0359)